High-dose intravenous immune globulin in the management of severe Guillain-Barré syndrome - Baskın, Esra; Türkay, Sadi; İçağasıoğlu, Dilara; Tanzer, Fatoş; Cevit, Ömer (The Turkish Journal of Pediatrics, 1996)
Guillain-Barré Syndrome (GBS) is the most common cause of acute generalized paralysis. Although the cause and pathogenesis of GBS remain unknown, there is increasing evidence to suggest that this syndrome has an immunological basis. Two children suffering from GBS were treated with high-dose Intravenous Immune globulin (IVIG) (1 g/kg/day over two consecutive days). Both children showed marked clinical improvement within 48 hours of the onset of treatment. It is suggested, on the basis of recent case reports, that Immunoglobulins may have an important role in the treatment of Guillain-Barré Syndrome.
Keywords: intravenous immunoglobulin; Guillain-Barré syndrome